Upaya Meningkatan Kapasitas Guru dalam Melakukan Asessmen di SLB Melalui Kegiatan Workshop - Khoirullah, Ihsan Marvel (Literal: Disability Studies Journal, 2023)
Increasing teacher capacity in carrying out assessments is crucial in special education units. Class teachers in special schools need to have the skills and courage to carry out informal assessments so that the learning program is appropriate to the students' conditions. This research aims to describe the implementation of increasing teacher capacity in conducting assessments in Special Schools. Data collection used a qualitative approach in the form of unstructured interviews, participant observation, and documentation studies. Data were analyzed by means of data reduction, data display, and drawing conclusions (Miles & Hubberman). The validity of this research data was carried out by data triangulation, researcher diligence, and member checking. The results of this research reveal that the assessment workshop process can be carried out in a flip class with online sessions for conceptual material related to assessment, while offline sessions are for practice in preparing instruments and implementing assessments. Teacher capacity building activities are indeed important, but their implementation requires effective and efficient arrangements so that teachers are ready to receive the material. However, it is recognized that the assessment workshop can provide teachers with an understanding of how to make instruments. The description of the implementation of the assessment workshop in this research can be used as a reference for managers of other special education institutions by emphasizing attention to better management of the implementation of activities.